DEMISE AND COHERENCE WITHIN HEGEL’S CONTINGENCY AND EXISTENCE - Stephen Curkpatrick (Sekolah Tinggi Teologi Sangkakala & Sekolah Tinggi Jemaat Kristus Indonesia, 2021)
Everything finite is finally contingent, yet contingency is durability within nature and more so, creativity within human existence. The thesis of this article, which is cast within Hegel’s relationship between necessity and contingency, is this: within aspirational fidelity and volitional integrity, loss and gain in human existence are not symmetrical; loss and gain are asymmetrical and so in principle, redemptive. Out of demise, by retrospective creativity, gain can surpass loss—a tacit christological perspective. Inspirited by human aspiration, creative possibilities are generated; movement, growth and change occur within a dialectical movement of moments exhibiting contradiction, mediation and novel development. Segala sesuatu yang terbatas akhirnya memiliki ketidakpastian. Namun kontingensi adalah daya tahan di dalam alam dan lebih dari itu, kontingensi merupakan kreativitas dalam keberadaan manusia. Tesis artikel ini, yang diutarakan dalam hubungan Hegel antara kebutuhan dan kontingensi, adalah ini: dalam kesetiaan aspirasional dan integritas kehendak, kerugian dan keuntungan dalam keberadaan manusia tidak simetris; kerugian dan keuntungan bersifat asimetris dan pada prinsipnya, begitu juga dengan penebusan. Karena kematian, dengan kreativitas retrospektif, keuntungan dapat mengalahkan kerugian — perspektif Kristologis. Terinspirasi oleh aspirasi manusia, kemungkinan kreatif dihasilkan; gerakan, pertumbuhan, dan perubahan terjadi dalam gerakan dialektika momen-momen yang menunjukkan kontradiksi, mediasi dan perkembangan baru.